Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae) - de Santana, Carlos David; Maldonado-Ocampo, Javier A. (Zootaxa, 2004)
A detailed examination of the types of the poorly known nominal gymnotiform apteronotid species Sternarchus mariae Eigenmann & Fisher and Sternarchus jurubidae Fowler, both described from localities in the Trans-Andean region of Colombia, was performed. This investigation resulted in a redescription of the former species, as well as a reevaluation of specific status of the latter. It is concluded that both taxa are valid within the currently recognized genus Apteronotus. The presence of A. eschmeyeri, A. mariae and A. magdalenensis supports the previous hypotheses of the Rio Magdalena Basin as a region of endemism.